2016
DOI: 10.1210/jc.2015-2687
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Ischemic Stroke: A Prospective Cohort Study and Meta-Analyses

Abstract: Extremely low endogenous testosterone concentrations were associated with high risk of IS in men, a risk mediated in part by body mass index and hypertension. Whether or not low testosterone is a causal factor for IS or merely a biomarker of poor metabolic health is still not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 39 publications
0
55
0
2
Order By: Relevance
“…Male hypogonadism is strongly associated with central adiposity, insulin resistance, MetS, type 2 diabetes, and stroke in multiple populations, although it remains unclear in many of these studies if low TT is causative or a biomarker of poor metabolic health (Holmegard et al, 2016, Moriarty-Kelsey et al, 2010, Traish, 2014, Zitzmann, 2009). Historically, many clinical features of KS, including cardiometabolic dysfunction, have been attributed to long-standing hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…Male hypogonadism is strongly associated with central adiposity, insulin resistance, MetS, type 2 diabetes, and stroke in multiple populations, although it remains unclear in many of these studies if low TT is causative or a biomarker of poor metabolic health (Holmegard et al, 2016, Moriarty-Kelsey et al, 2010, Traish, 2014, Zitzmann, 2009). Historically, many clinical features of KS, including cardiometabolic dysfunction, have been attributed to long-standing hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported negative associations between low testosterone levels and the risk of ischemic stroke and of all-cause, CVD, and cancer mortality; the question of whether these associations are causal, or whether testosterone is an important biomarker of overall male health, has yet to be fully investigated (Haring et al 2010;Holmegard et al 2016).…”
Section: Effects Of Testosteronementioning
confidence: 99%
“…A limited number of follow-up studies have focused on testosterone levels and stroke and the results have been conflicting (33)(34)(35)(36). The study by Yeap et al observed a protective effect of testosterone on the risk of stroke.…”
Section: Cardiovascular Diseasementioning
confidence: 99%